Pengaruh Metode Tebak Kata Terhadap Peningkatan Keterampilan Berbicara Bahasa Arab Di Madrasah Diniyah Al-Hidayah Gempol Pasuruan - Syarifuddin; Mufidatul Munawaroh (Universitas Yudharta Pasuruan, 2020)
Based on observation, students of Madrasah Diniyah Al-Hidayah Gempol Pasuruan are not good enough in mastering Arabic language, especially in speaking skill. Researchers tried to solve the problemby using the Word Guess method. Researchers use the method is to know the influence of the method in speaking skill of students in Madrasah Diniyah Al-Hidayah Gempol Pasuruan. This research is quantative research. The population of this research is all of the 3rd grade students of Madrasah Diniyah Al-Hidayah Gempol Pasuruan. The data collection techniques in this study use observations, interviews, documentation and tests. This study shows that there is influence of the Word Guess method in improving students’speaking skill in Madrasah DiniyahAl-Hidayah Gempol Pasuruan based on the number paired samples statistic of the pretest and the post-test using T-Test.